2017
DOI: 10.1007/s00445-017-1188-7
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a spatter-rich pyroclastic density current deposit in a Neogene sequence of trachytic-mafic igneous rocks at Mason Spur, Erebus volcanic province, Antarctica

Abstract: Erosion has revealed a remarkable section through the heart of a volcanic island, Mason Spur, in the southwestern Ross Sea, Antarctica, including an unusually well exposed section of caldera fill. The near-continuous exposure, 10 km laterally and >1 km vertically, cuts through Cenozoic alkalic volcanic rocks of the Erebus volcanic province (McMurdo Volcanic Group) and permits the study of an ancient volcanic succession that is rarely available due to subsequent burial or erosion. The caldera filling sequence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…TAM-transantarctic mountains (stippled ornament) comprehensive reassessment of the volcanic evolution to be made. An important result of our study is the discovery of a thick caldera-filling sequence of ignimbrites, reported initially by Martin et al (2018). Similar deposits are very rare and much less voluminous elsewhere in the WARS and our study thus fills a significant gap in our knowledge of the eruptive and structural evolution of the large polygenetic WARS volcanoes.…”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…TAM-transantarctic mountains (stippled ornament) comprehensive reassessment of the volcanic evolution to be made. An important result of our study is the discovery of a thick caldera-filling sequence of ignimbrites, reported initially by Martin et al (2018). Similar deposits are very rare and much less voluminous elsewhere in the WARS and our study thus fills a significant gap in our knowledge of the eruptive and structural evolution of the large polygenetic WARS volcanoes.…”
Section: Introductionsupporting
confidence: 65%
“…Mason Spur represents one of the early stages of volcanism of the Mount Morning Volcanic Field. Previous geological studies of Mason Spur were a PhD project by Wright-Grassham (1987; a brief summary is given by Wright and Kyle 1990) and papers by Martin et al ( , 2013Martin et al ( , 2018. The study by Wright-Grassham (1987) was reconnaissance in nature and investigated Mount Discovery, Mount Morning and Minna Bluff in addition to Mason Spur.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 3 more Smart Citations